Pengaruh Kepemimpinan Kepala Desa Terhadap Peningkatan Kesadaran Masyarakat Dalam Membayar Pajak Bumi dan Bangunan di Desa Kaayuran Bawah Kecamatan Langowan Selatan Kabupaten Minahasa - Kalalo, Frisilia Jolanda; Tulusan, Femmy; Ruru, Joorie (Sam Ratulangi University, 2015)
Abstract: This study berwal of experiences to the principal that is, the extent to which the influence of theleadership of the head of the village to increase public awareness in paying taxes on land and buildings inthe village kaayuran south district under the District Langowan minahasa. Thus this study aims to analyzethe influence of the leadership of the head of the village to increase public awareness in paying taxes on landand buildings in the village kaayuran south district under the District Langowan minahasa. This study usesquantitative methods to approach the descriptive analysis of data and information collected throughquestionnaires distributed to the technique 53 respondents were equipped with observation technique byapplying the technique of frequency tables, analysis of product moment and simple linear regression. Basedon the results of the data analaisi known that the answer respoenden on leadership clod village is in a classinterval between 22-25 with a .ï‚±frequency of 25 respondents, or 47.2% This indicates that the average scoreof variable Leadership Village Head (X) are in the category of